PRÉCIS OF HUNGARIAN PAREMIOGRAPHY AND PAREMIOLOGY - Voigt, Vilmos (Proverbium - Yearbook, 2013)
This is a review essay on the rich accomplishments of Hungarian paremiography and paremiology. There exists a long history of Hungarian proverb collections, and while many of them deal primarily with national or regional Hungarian proverbs, there are also numerous collec-tions that include comparative materials from other European languages. It is shown that many aspects of culture, ethnography, folklore, and history are contained in the proverbial materials. The article also includes comments on genre issues, the classification system used in the collections, and their use for educational purposes. Of course, issues of linguistics and semantics are also discussed. An important bibliography of the accomplishments of Hungarian proverb research is attached as well.